2021
DOI: 10.1109/tse.2018.2884911
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Feature Scattering in the Linux Kernel

Abstract: Feature code is often scattered across a software system. Scattering is not necessarily bad if used with care, as witnessed by systems with highly scattered features that evolved successfully. Feature scattering, often realized with a pre-processor, circumvents limitations of programming languages and software architectures. Unfortunately, little is known about the principles governing scattering in large and long-living software systems. We present a longitudinal study of feature scattering in the Linux kerne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…Of course, the project partners are also very active in the scientific community. With more than 50 publications, the project has had a significant impact on the state of the art, with notable publications at ASE [20] , Isola [21] , MODELS [22] as well as in IST [22], [23] , TSE [24] and many others. Members of the project have also organised the main scientific event of the product line engineering community, SPLC in Gothenburg in 2018, with well over 100 participants and workshops and tutorials geared directly towards the topics of the projects.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the project partners are also very active in the scientific community. With more than 50 publications, the project has had a significant impact on the state of the art, with notable publications at ASE [20] , Isola [21] , MODELS [22] as well as in IST [22], [23] , TSE [24] and many others. Members of the project have also organised the main scientific event of the product line engineering community, SPLC in Gothenburg in 2018, with well over 100 participants and workshops and tutorials geared directly towards the topics of the projects.…”
Section: Discussionmentioning
confidence: 99%
“…To the left, the code is cloned and adapted (one line changed in the branch BC+SmallDisplay); to the right, a configuration option represents the change in a common codebase (integrated platform). The changes are usually more complex (e.g., features can be highly scattered [40], [41]), as well as the representation of variability in the integrated platform. We also need more variability concepts, among others, features [42], [43], [44], codelevel configuration [10], feature-to-asset traceability [14], [15], [45], a feature model (a hierarchical structure with features and their dependencies) [12], [13], a configurable build system [10], and a configurator tool [16], [46], [47].…”
Section: A Motivating Running Examplementioning
confidence: 99%
“…In total, we received 152 responses from 1, 012 email requests (15.01% response rate). Previous studies in Software Engineering field have have reported response rates between 5.7% [60] and 7.9% [49]. We discarded 22 partial responses, which left us with 130 responses (12.9% response rate after excluding the partial responses).…”
Section: Data Collectionmentioning
confidence: 99%